Infectious Diseases and Some Factors Associated with Healthy Life Expectancy in the Globe: A Systematic Review (Bangladesh Journal of Infectious Diseases, 2023)
Background: Healthy life expectancy (HALE) at birth measures the standard of living anticipated.Objective: The purpose of this study was to identify the main global risk factors for HALE at birth.Methodology: The data of 212 countries have been extracted from the data hub of World Health Organization, Worldometer, World Bank, and United Nations. The HALE at birth was considered as the dependent variable and the death rate due to Coronavirus disease 2019 (COVID 19), recovery rate from COVID 19, tuberculosis (TB) incidence, universal health coverage (UHC) service index, tobacco smoking, alcohol consumption rate, human immunodeficiency virus (HIV) prevalence rate, average household size, gross domestic product (GDP), and current health expenditure were considered as the independent variables. Descriptive statistics, Pearson’s correlation analysis, and multiple linear regression model were used as the statistical tools to analyze the data.Results: The study results revealed that the HALE is found lowest in Central African Republic (44.9 years) and highest in Singapore (76.2 years). On the other hand, the death rate due to COVID 19 is found highest in Nicaragua (32.0%). In case of the recovery rate from COVID 19, the lowest value is seen in Tajikistan (0.0). Again, the lowest UHC service index is found in Montserrat (0.0). Alcohol consumption rate is found highest in Moldova Republic (15.20). In case of HIV prevalence rate, the highest value is seen in Eswatini (27.30). Average household size is seen highest in Senegal (8.30). The recovery rate from COVID 19, UHC service index, GDP, current health expenditure TB incidence, tobacco smoking, HIV prevalence rate and average household size were significantly correlated with the HALE at birth. Again, the multiple linear regression model identified the UHC service index, alcohol consumption rate, HIV prevalence rate and average household size as the significant factors which are responsible for the variation in HALE at birth worldwide.Conclusion: The UHC service index, alcohol consumption rate, HIV prevalence rate and average household size are the most associate factors of HALE at birth globally.Bangladesh Journal of Infectious Diseases, December 2022;9(2):59-68